PENERAPAN WEBSITE PROMOSI WISATA AIR TLAGA PESONA DI DESA TLAGAYASA BERBASIS WORDPRESS - Aminuddin, Jamrud; Saputra, Dian Rizqi; Azmi, Ulil; Shokib, Maskhiyatus (LPPM Universitas Nusa Mandiri, 2025)
Tlagayasa Village, located in Bobotsari Sub-district, Purbalingga Regency, Central Java, is situated about 30 km from the Department of Physics, Faculty of Mathematics and Natural Sciences, UNSOED. Based on interviews with village officials, a water tourism destination with various attractions is currently being developed. However, despite progress in physical facilities, plans for proper tourism promotional media remain unprepared. The village government, in coordination with the Faculty of Mathematics and Natural Sciences, UNSOED, identified limited knowledge of promotional strategies and the absence of a digital database as major challenges. To address this issue, village officials requested assistance in developing online promotional media. Considering the rapid advancement of information technology, digital platforms play a crucial role in supporting tourism promotion. Through community service activities, several stages were implemented, including socialization, training, mentoring, and evaluation. The initial stage involved data collection and website development using WordPress, followed by training for BUMDes Tlaga Pesona managers. Mentoring was then conducted to enable them to manage the website independently. Evaluation results showed that the website improved the managers’ digital literacy, sense of ownership, and responsibility for sustainable tourism promotion. This program demonstrates the tangible benefits of academic–community collaboration and provides a replicable model for technology-based tourism development in rural areas.